2008
DOI: 10.1177/0886260508319366
|View full text |Cite
|
Sign up to set email alerts
|

Rape Prevention With College Men

Abstract: This study evaluates the effectiveness of a theoretically based rape prevention intervention with college men who were at high or low risk to perpetrate sexually coercive behavior. Participants (N = 146) are randomly assigned to the intervention or control group. Outcomes include rape myth acceptance, victim empathy, attraction to sexual aggression, sex-related alcohol expectancies, and behavioral indicators, measured across three time points. Positive effects are found for rape myth acceptance, victim empathy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
76
4

Year Published

2010
2010
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(87 citation statements)
references
References 37 publications
(52 reference statements)
7
76
4
Order By: Relevance
“…A very promising finding of this study is that, for the total sample, participants' self-reported sexually coercive behaviors significantly decreased from pretest to follow-up survey 5 weeks later, which is contrary to the few studies that have included behavioral measures of sexually coercive behaviors (Foubert, 2000;Stephens & George, 2009). If this program can effect positive changes in participants' self-reported sexually coercive behaviors, then it is effectively reducing the total amount of sexually coercive behavior occurring within that community, in this case fraternity members, which in turn would lead to an overall reduction in sexual violence among fraternity members at this university.…”
Section: Discussioncontrasting
confidence: 71%
“…A very promising finding of this study is that, for the total sample, participants' self-reported sexually coercive behaviors significantly decreased from pretest to follow-up survey 5 weeks later, which is contrary to the few studies that have included behavioral measures of sexually coercive behaviors (Foubert, 2000;Stephens & George, 2009). If this program can effect positive changes in participants' self-reported sexually coercive behaviors, then it is effectively reducing the total amount of sexually coercive behavior occurring within that community, in this case fraternity members, which in turn would lead to an overall reduction in sexual violence among fraternity members at this university.…”
Section: Discussioncontrasting
confidence: 71%
“…Participants were asked to rate on a scale of 1 to 7 whether they would force a woman to do something sexual that she did not want to do, if they themselves could be assured that they would not be caught or punished. This has been used in many studies as a measure of behavioral intent to commit sexual assault (Abrams, Viki, Masser, & Bohner, 2003;Murnen, Wright, & Kaluzny, 2002;Stephens & George, 2009). Men in the present study who viewed pornography, no matter what type (mainstream, rape, and sadomasochistic) all were significantly more likely to indicate a willingness to commit sexual assault than men who chose not to view pornography.…”
Section: Discussionmentioning
confidence: 75%
“…Research from the USA with men in college attending rape prevention programmes suggests that these show less impact on men at higher risk of raping. 58 Violence prevention with men is very unlikely to be optimised with a one size fits all intervention. Men who perpetrate the most severe violence against women often do not see themselves as bound by social norms 34,36 .…”
Section: Involving Boys and Men In Violence Preventionmentioning
confidence: 99%